Association Between Personal Protective Equipment Use and Laboratory-Confirmed Onychomycosis Among Farmers - Imam Jalaludin; Jaova Layla (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Onychomycosis has been reported as common in occupations involving prolonged exposure to moist soil; however, the association with personal protective equipment (PPE) requires more rigorous methodological consideration. This cross-sectional study included 33 farmers in Sumbaga Village, Bumijawa District, Indonesia. Direct microscopy using Lactophenol Cotton Blue and culture on Sabouraud Dextrose Agar were performed to detect fungal elements, and participants were categorized according to self-reported PPE use. Fifteen participants reported using PPE, while 18 did not. Laboratory positivity was identified in 11 of 15 PPE users (73.3%) and 18 of 18 non-users (100%). The observed distribution indicates a lower proportion of positive findings among PPE users; however, this association should be interpreted with caution. Analysis using Fisher’s exact test indicated a statistically significant association between PPE use and onychomycosis (p = 0.033). Fungal isolates showing morphological characteristics consistent with Trichophyton rubrum, Trichophyton mentagrophytes, Aspergillus sp., Fusarium sp., and Scopulariopsis brevicaulis were identified. However, as participants were partly selected based on nail discoloration and non-dermatophyte fungi were identified without repeat isolation criteria, these findings reflect suspected cases within the sampled population and should not be interpreted as population-level estimates or evidence of causal protection; future studies should employ more representative sampling strategies, validated measurement of PPE exposure, and adjustment for relevant confounding factors to improve inferential validity.